Interaction between recrystallization and strain-induced precipitation in a high Nb- and N-bearing austenitic stainless steel: influence of the interpass time - Silva, M. B. R.; Gallego, J. [UNESP]; Cabrera, J. M.; Balancin, O.; Jorge, A. M. (Elsevier B.V., 2015)
In this work, we studied the influence of the interpass time (20 and 5 s) on the interaction between recrystallization and strain-induced precipitation occurring during multiple passes'deformations under continuous cooling conditions in a high niobium- and nitrogen-bearing austenitic stainless steel (ISO 5832-9). The correlation between microstructure evolution and hot mechanical properties was performed by physical simulation using hot torsion tests. The microstructure evolution was analyzed by optical microscopy, transmission electron microscopy and electron back scattered diffraction (EBSD). This technique indicated that dynamic recrystallization occurred at the first passes promoting an excellent grain refinement. On the other hand, shorter interpass time (5 s) allowed higher volume fraction of smallest precipitates than larger interpass time (20 s). After soaking, only TiNbN precipitates were found, whereas, Z-phase (CrNbN) and NbN were formed during thermomechanical processing. Particles with sizes between 20 and 50 nm were effective to pin grain boundaries and dislocations. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Hot mechanical behavior; Recrystallization; Grain refinement; Niobium; Precipitation; Stainless steel